Investigative assets: the CPA's role in detecting and preventing fraud. - Slotter, Keith (FBI Law Enforcement Bulletin, 1999)
The role of the certified public accountant (CPA) role in detecting and preventing fraud is discussed. The level of fraud being perpetrated against corporate America and the public outcry about it has meant that CPAs have been forced to alter the way in which they conduct business in order to make the search for fraud a specific requirement in each audit engagement undertaken. Such a change represents a new opportunity for law enforcement to work with the accounting profession to detect, prevent, and investigate an array of financial crimes long before companies report such fraud for criminal investigation. The traditional role of auditors; how the accounting industry began to change its role in the wake of the savings and loan crisis in the 1980s to reduce risk of litigation for negligent conduct and oversight and to enhance law enforcement cooperation; the fact that CPAs now have to plan their audits to detect and report material fraud to company management; and the successful liaison that now exists between law enforcement and public accounting are discussed.